Sports branding as an object of scientific analysis based on the study of publications in the international scientometric database Scopus - Svitlana Stadnyk; Daria Okun; Anastasia Bondar; Natalia Sereda (Kharkiv State Academy of Physical Culture, 2023)
Background and Study Aim: Sports branding is a systematic process of communication with a mass audience, aimed at creating a special sports culture: understanding the need to maintain a healthy lifestyle; maintaining interest in sports activities; formation of a positive image of the country through large-scale events, etc. Branding technologies are currently actively used not only by sports clubs, individual athletes, public authorities, but also by non-profit physical culture and sports organizations. Thus, this study was aimed at systematizing modern scientific ideas about sports branding. The purpose is a bibliometric analysis of sports branding research based on the study of publications in the international scientometric database Scopus. Material and Methods: the literature on sports branding included in the Scopus database for the period from 1999 to 2023 was studied. Bibliometric methods of information processing were used in the context of sports branding. VOSviewer software was used for visual analysis in terms of publication, author, country, journals, citations and keywords with bibliometric mapping, visualization of cluster density, citation weights. Results: after verification, a total of 160 publications from the Scopus database were included. The largest number of works relate to the following areas of research: Business, Management and Accounting, Social Sciences, etc. The leading country in terms of publication activity is the United States with 59 publications. As for the authors, Y. Dubinsky and A. Richelieu have published the largest number of works and made a great contribution to the study of sports branding. The biggest keyword cluster was sports, and the most popular keywords in recent years were: social media, branding, destination branding, sport tourism, content analyses, etc., which provides ideas for further research in this area. Conclusions: the constructed bibliometric maps made it possible to determine the most popular areas of research to study the problem under study: sports branding as an effective tool for forming the country's image; branding of sports events; social media as a tool for sports branding; the importance of brands in the professional sports industry; athletes personal branding. The use of the VOSviewer program, version 1.6.18, made it possible to provide a comprehensive analysis of the problem, to identify priority research areas in this area: the principles of using sports branding as a mechanism for constructing a territorial brand, as well as technologies for promoting sports brands in social media.